Healing Attachment and Strengthening Emotional Regulation among Young Adults with a History of Broken Home Experiences - Diah Pramudhita K; Cecillia Jiniputri Novean Dumatubun; Muhammad Iksan A; Zidni Salma Fauza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to identify the psychological impact of growing up in a broken home on a young adult and to develop an intervention to promote attachment healing and emotion regulation. The assessment was conducted with participant F, a 25 year old woman, using observation, in-depth interviews, and document analysis. The findings indicate that the participant experienced difficulties in regulating emotions, tended to suppress her feelings, and exhibited low interpersonal trust as a result of maternal loss and prolonged family conflict. The intervention consisted of psychoeducation, expressive writing, emotion regulation training, assertive communication, and strengthening social support. The intervention outcomes demonstrated improvements in self-awareness, emotional expression, and the adoption of more adaptive emotion regulation strategies.